SAVAKLARDA KRET ŞEKLİNİN DEBİ KATSAYISINA ETKİSİNİN İNCELENMESİ - DOĞAN, YUSUF (Fırat Üniveristesi, 2009)
Bu çalışmada, savaklarda kret şeklinin debi katsayısına etkisi incelenmiştir. Aynı zamanda savaklar ve savakların karakteristik özellikleri hakkında bilgi verilmiştir. Çalışmada dört adet farklı geometrik yapıya sahip savak kret şekli için bir dizi deneysel çalışma yapılmıştır. Savaklar üzerinden geçen debi, nap yükü ve akım hızları belirlenmiştir. Elde edilen sonuçlar tartışılmış ve yapılan çalışma sonucunda savak kret şeklinin debi katsayısı üzerinde etkili bir parametre olduğu görülmüştür. ¼ yuvarlatılmış kret şekline sahip doğrusal savağın en büyük debi katsayısı değerlerine sahip olduğu tespit edilmiştir.

In this study, the effect of weir crest shape on the discharge coefficient was studied as experimentally. Also, the knowledge related to the weirs and their flow characteristics was given in the study. In the study, a series of experiments were conducted for the straight weirs having four different geometrical shapes. Flow rate, nappe height and flow velocity were measured in the laboratory experiments. Obtained results were discussed. As a result, it was indicated that the crest shape was a very important parameter for discharge coefficient of the weir. ¼ rounded crest shape has higher discharge coefficient values than those of the other crest shape tested.
Investigation of the effect of discharge coefficient on the weir crest shape
Keywords: İnşaat Mühendisliği